The impact of teaching the circle unit to the students of the first grade secondary using blending learning through discovery and e-learning strategy on academic achievement - El Sayed, Hussain Ismail Mohamed (Arab Journal for Sciences and Research Publishing, 2016)
Aim: To assess the extent of the students’ learning of the circle unit when being taught through a strategy blending learning through discovery and learning attained electronically. Study Methodology: The study followed the quasi- experimental method, which is based upon the design of two groups: an experimental and an equivalent control group, with the application of the pre- and post-measurements to verify the validity of the hypotheses with the aim of reaching a comprehensive understanding of the extent of impact a teaching strategy based upon blending learning through discovery and learning attained electronically might have on the achievement of the students’ learning of the circle unit. Study Population: They were the first-year secondary school students officially registered for the year 1432/33 H. at the Gunfuthah Governorate. Study Sample: Consisted of Ibn Majah first – year secondary school students at Guz center, Al-Gunfutha Governorate, for the school year 1432/33 H, and numbering (51) students in all: (24) were in the control group studying according to the traditional method; and (27) in the experimental group which had been taught following the teaching strategy of blending learning through discovery and learning electronically in their learning of the circle unit. Study Tools: 1. An achievement test measuring learning at Bloom’s first two levels: Recall and Comprehension. 2. The statistical treatment was performed using the Statistical Package for Social Sciences (SPSS). Used Statistical Techniques: t- test for comparing the mean scores of the achievements of the experimental group students (who learned the circle unit according to the investigated teaching strategy) and the control group students (who had been taught the circle unit traditionally); Cronbach alpha index for reliability; Levine test to ensure variance homogeneity; and holist agreement equation. Most Important Results: There were statistically significant differences at the level (0.001) between the experimental and control groups in behalf of the experimental students who learned the circle unit according to a teaching strategy based on blending learning earned through discovery and learning gained electronically in respect of (1) total achievement (2) achievement of the Recall Level and (3) achievement of the Comprehension Level. Important Recommendations: • Stressing the need to employ the teaching strategy of blending learning through discovery and learning through electronic devices when teaching the circle unit, in place of the conventional method of instruction. • Training mathematics teachers in designing computer software conducive to the implementation of the strategy of blending learning by discovery with learning gained electronically when teaching mathematics subject. • Working to restructure and reformulate the contents of present mathematics subject in line with modern instructional technology with the purpose of materializing mathematical concepts making them more stimulating and motivating for self-learning.